http://webwork1.math.utah.edu/webwor...a08e031f41.png has the solution x=

Printable View

- November 6th 2009, 08:07 PMthebristolsoundLogarithm Equation
http://webwork1.math.utah.edu/webwor...a08e031f41.png has the solution x=

- November 6th 2009, 08:17 PMDefunkt
- November 6th 2009, 08:20 PMDebsta
Recall the rule lnA - lnB =ln(A/B). Apply that to LHS.

Then you'll have ln [(x+1)/(x-2)} = ln x

Drop the lns so that (x+1)/(x-2)=x

This becomes x+1 = x(x-2) which gives a quadratic and go from there.

Remember to check your answers from the quadratic in the ORIGINAL log equation. Reject answers which don't give pos values for x+1, x-2 or x as ln A is not defined for non-positive A valus.